2018
DOI: 10.3390/molecules23020353
|View full text |Cite
|
Sign up to set email alerts
|

VSpipe, an Integrated Resource for Virtual Screening and Hit Selection: Applications to Protein Tyrosine Phospahatase Inhibition

Abstract: The use of computational tools for virtual screening provides a cost-efficient approach to select starting points for drug development. We have developed VSpipe, a user-friendly semi-automated pipeline for structure-based virtual screening. VSpipe uses the existing tools AutoDock and OpenBabel together with software developed in-house, to create an end-to-end virtual screening workflow ranging from the preparation of receptor and ligands to the visualisation of results. VSpipe is efficient and flexible, allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…This sequence, together with the structure of the C. albicans orthologue (CaMetH) (PDB ID 4L65 ; doi:10.1016/j.jmb.2014.02.006), was used to create the molecular homology model in Modeller (v9.23) ( 110 ) with the basic option mode. The AfMetH model was then used for virtual screening with the semiautomated pipeline VSpipe ( 111 ). For comparison, we also performed virtual screening with the structure of the human methionine synthase containing the folate and homocysteine binding domains (PDB ID 4CCZ ).…”
Section: Methodsmentioning
confidence: 99%
“…This sequence, together with the structure of the C. albicans orthologue (CaMetH) (PDB ID 4L65 ; doi:10.1016/j.jmb.2014.02.006), was used to create the molecular homology model in Modeller (v9.23) ( 110 ) with the basic option mode. The AfMetH model was then used for virtual screening with the semiautomated pipeline VSpipe ( 111 ). For comparison, we also performed virtual screening with the structure of the human methionine synthase containing the folate and homocysteine binding domains (PDB ID 4CCZ ).…”
Section: Methodsmentioning
confidence: 99%
“…Our approach to assess the druggability of the AfPPases was based on a combination of virtual screening with VSpipe [15] and pocket analysis with PockDrug [17] in order to identify suitable druggable sites for drug development on the essential AfPPases. Currently, there are no available 3D structures of any of these AfPPases, thus, we had to generate molecular homology models for the virtual screening.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that the virtual screening tool VSpipe could be used to identify functional ligand binding sites in the human phosphatase PTP1B, as well as to guide the selection of initial hits for drug discovery [15]. The blind docking option in VSpipe is useful when there is no previous knowledge about the functional sites on the target protein, as is the case for the AfPPases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence together with the structure of the C. albicans orthologue (CaMetH) (PDB ID: 4L65, DOI: 10.1016/j.jmb.2014.02.006) were used to create the molecular homology model in Modeller (version 9.23) (106) with the basic option mode. The AfMetH model was then used for virtual screening with the semi-automated pipeline VSpipe (107). For comparison we also performed virtual screening with the structure of the human methionine synthase (hMS) containing the folate and homocysteine binding domains (PDB ID: 4CCZ).…”
Section: Molecular Homology Models and Virtual Screeningmentioning
confidence: 99%